2018
DOI: 10.1155/2018/4136253
|View full text |Cite
|
Sign up to set email alerts
|

Sofosbuvir Based Regimens in the Treatment of Chronic Hepatitis C with Compensated Liver Cirrhosis in Community Care Setting

Abstract: Background Direct-acting antiviral (DAA) drugs have been highly effective in the treatment of chronic hepatitis C (CHC) infection. We aim to evaluate the treatment response of Sofosbuvir based DAA in CHC patients with compensated liver cirrhosis as limited data exists in the real-world community setting. Methods All the CHC patients with compensated liver cirrhosis treated with Sofosbuvir based DAAs between January 2014 and December 2017 in a community clinic setting were retrospectively analyzed. Pretreatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 28 publications
1
14
0
Order By: Relevance
“…This result highlights the potency of DAAs in HCV elimination, a finding that is following the previously published results [15]. Despite the proven potency of DAAs in patients with liver cirrhosis [16], the SVR12 among patients with cirrhosis in the current study was relatively low (71.4%) although all the cirrhotic patients were Child–Pugh class A; this could be explained by the low number of cases ( n = 14).…”
Section: Discussionsupporting
confidence: 86%
“…This result highlights the potency of DAAs in HCV elimination, a finding that is following the previously published results [15]. Despite the proven potency of DAAs in patients with liver cirrhosis [16], the SVR12 among patients with cirrhosis in the current study was relatively low (71.4%) although all the cirrhotic patients were Child–Pugh class A; this could be explained by the low number of cases ( n = 14).…”
Section: Discussionsupporting
confidence: 86%
“…The treatment of HCV has shifted toward more tolerable, safer oral regimens with the use of direct-acting antiviral agents (DAAs). These regimens have truly revolutionized the efficiency of HCV treatment by achieving a sustained virologic response (SVR), shortening the duration of treatment, and improving patient outcomes without the burden of neuropsychiatric adverse effects [11,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the clinical examination, we found that 95% of our study group showed no signs of hepatic decompensation, while 2% of them had ascites and lower limb oedema, 1% had ascites, 1% had jaundice, and 1% had lower limb oedema only. This could be explained by the fact that one patient developed HCC post-DAAs with further decompensation [15].…”
Section: Discussionmentioning
confidence: 99%